Memory N.D. Kosov - Team, Editorial (Recent Contributions to Physics, 2013)
Nikolai Kosov (1922-1995) – Kazakhstan’s physicist, an acknowledged expert in the field of heat – mass transfer and thermal physics, Honored Scientist of the Kazakh SSR (1984), Doctor of Physical and Mathematical Sciences (1972), Professor (1974).